Surrender - O'Hare, Brian (Author) (Syracuse University Press, 2022)
"Surrender takes readers on a journey into the heart of the American hero myth, from the Friday night football fields of Western Pennsylvania to a battalion of Marines in the Persian Gulf. But what happens when the crowds stop cheering and the 'Welcome Home Hero' parades are over? Guilt, fear and brutality collide with love and acceptance as a diverse tribe of characters struggle to reconcile mythology with reality, and to find meaning in a uniquely American chaos"--